Targeting the amyloid precursor protein interactome in Wnt signalling provides novel therapeutic strategies for Alzheimer’s disease - Elliott, Christina (Pharmakeftiki, 2025)
Alzheimer’s disease (AD) is characterised by progressive synaptic dysfunction, cognitive decline, and pathological hallmarks including amyloid-beta (Aβ) accumulation and tau hyperphosphorylation. Aβ disrupts Wnt signalling by inducing Dickkopf-1 (Dkk1); a secreted antagonist that promotes a pathological shift from canonical Wnt/β-catenin to non-canonical planar cell polarity signalling. Crucially, the amyloid precursor protein (APP) interacts with key components of the Wnt pathway, including the co-receptor LRP6 (low-density lipoprotein receptor-related protein 6). This places APP at the centre of a regulatory network – the APP interactome – that modulates synapse stability, Aβ production, and transcriptional homeostasis. In our recent studies, we explored how therapeutic modulation of this network restores synaptic health and cognitive function in AD models. We show that the ROCK (Rho-associated coiled-coil kinase) inhibitor fasudil reverses AD-associated transcriptional signatures in vivo and blocks Aβ-induced synaptotoxicity. Furthermore, we report a novel Dkk1-LRP6 disruptor peptide that restores canonical Wnt signalling, reduces Aβ generation, and prevents cognitive deficits in vivo. These data position the APP-Wnt interactome as a rich source of therapeutic targets, and establish new strategies for the restoration of synaptic resilience in AD.